(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purposes of this research were 1) to study the context and potential of self-management in the local social and health of the community in Khwao Sinarin district, Surin province, 2) to study the process of creating a community charter in arts and culture for health in Khwao Sinarin district, Surin province and 3) to present a community charter for the health of the community according to the Buddhist principle in Khwao Sinarin district, Surin province. Action research and quantitative research were used and research tools were interview form and questionnaires. Data were collected from the in-depth interview, focus group discussion. Qualitative data from 13 key informants were analyzed by using content analysis whereas quantitative data collected from 327 samples were analyzed by using descriptive statistics. Results indicated that the villagers in this district are mostly females, 60 years old, average income 5,001-10,000 Baht, agricultural career, self-management potential in local arts and culture of community in this district found that overall is very high. The process of creating a community statute on the arts and culture for health along with the condition of welfare in this district has 7 steps: the first step, holding a local forum, step 2 common responsibility, step 3 establish community committee, step 4 agreement rules of coexistence, step 5 meeting to revise community statute draft, step 6 enactment of the statute, and 7 steps of the community’s arts and culture is published and distributed to the villagers for the creation of and to present a community charter for the health of the community according to the Buddha-dhamma in this district from the co-operation of the public sector, civil society. The establishment of a community committee, drafting the community statute by bringing the condition of welfare the unity of the villagers in the community the bases of sympathy justice for mutual relief, and the principle of 4 Bhavana to improve the quality of life of people in the community, and the use of the art and culture’s charter for the health of the community in the local area.